Positron Emission Tomography/Computerized Tomography (PET/CT) in Head and Neck Tumors - Koç, Zehra Pınar; Balcı, Tansel Ansal (Fırat University, 2011)
Objective: PET/CT is gaining acceptance in staging head and neck tumors in routine practice. Capability of PET/CT to scan whole body, affinity to head and neck tumors and accurate characterization of lymph nodes makes staging easier with PET/CT. In this study, we investigated the importance of PET/CT in staging of head and neck tumors. Materials and Methods: Nineteen patients with head and neck tumors (11 M, 8 F; mean: 50,4±17 years old) were included to the study. PET/CT results of patients were evaluated with follow-up results or histophology as the gold standard. Results: The patients were presented as thyroid carcinoma 3, laryngeal carcinoma 3, etiology of lymphadenopathy 1, lip or palatal tumor 3, mass characterization 3, proximal esophagus carcinoma 2, parotis tumor 3 and facial malign melanoma 1 patient. PET/CT identified residual or recurrent tumor in 4 patients, mass in 9, lymph node invasion in 5 and in one patient no residual disease. In whole group total 11 lymph node invasion and 6 distant metastasis were identified. Primary site of patient who had lymph node metastasis weren't found with PET/CT. Conclusion: Because of the capability of whole body definition and accurate lymph node staging of PET/CT and remarkable FDG affinity of head and neck tumors, PET/CT is a preferable imaging method. Considering general limitations and limitations which are specific to head and neck region of PET/CT; PET/CT can be used for staging and identification of head and neck tumors with high accuracy.

Amaç: Baş ve boyun tümörlerinde evrelemede PET/BT giderek artan oranda rutin kullanıma girmektedir. PET/BT tüm vücudu tarama olanağı sağlaması ve baş-boyun tümörlerinde tutulum göstermesi ve lenf nodlarını doğru bir şekilde karakterize etmesi bakımından evrelemede kolaylık sağlamaktadır. Bu çalışma ile baş ve boyun tümörleri olan hastalarda evrelemede PET/BT'nin önemini araştırdık. Gereç ve Yöntem: Çalışmaya baş ve boyun tümörü olan 19 hasta (11 E, 8 K; ortalama yaş;50.4±17) dahil edilmiştir. Hastalara yapılan PET/BT sonuçları altın standart takip sonucu veya histopatoloji alınarak değerlendirilmiştir. Bulgular: Çalışmaya dahil edilen hastalardan 3 tanesi tiroid karsinomu, 3'ünde larenks karsinomu, 1'inde boyunda lenfadenopati etyolojisi, 3'ünde dil-damakta kitle, 3'ünde boyunda kitle karakterizasyonu, 2'sinde proksimal özefagus karsinomu, 3'ünde parotis tümörü ve 1 hastada yüzde malign melanom nedeniyle PET/BT yapılmıştır. PET/BT hastalardan 4 tanesinde rezidü/nüks ve 9'unda kitle lezyonu tanımlamış, 5'inde lenf nodu yayılımını ve bir hastada rezidü veya nüks olmadığını göstermiştir. Bütün hasta grubunda toplam 11 hastada lenf nodu invazyonu ve 6 hastada uzak metastazı göstermiştir. Patolojik lenfadenopati nedeniyle gönderilen bir hastada ise primeri belirleyememiştir. Sonuç: PET/BT baş boyun tümörlerinin değerlendirilmesinde rahatlıkla kullanılabilecek bir yöntemdir. Yöntemin gerek bu bölgeye özgü gerekse genel sınırlılıkları göz önünde bulundurularak yüksek doğrulukla kitle tanımlama ve evreleme için kullanılabilir.
Baş ve Boyun Tümörlerinde Positron Emisyon Tomografi/Bilgisayarlı Tomografi (PET/BT)